Treatment wetlands - Kadlec, Robert H. (Lewis Publishers, 1995)
Completely revised and updated, Treatment Wetlands, Second Edition is still the most comprehensive resource available for planning, designing, and operating wetland treatment systems. It provides engineers and scientists with a complete reference source that includes: detailed information on wetland ecology, design for consistent performance, site specific studies, estimated costs, construction guidance and operational control through effective monitoring. Case histories of operational wetland treatment systems illustrate the variety of design approaches presented allowing readers to tailor them to the needs of their projects.